Improved Left-Corner Chart Parsing for Large Context-Free Grammars (Revised Version) - Moore, Bob (Kluwer Academic, 2004)
We develop an improved form of left-corner chart parsing for large context-free grammars, introducing improvements that result in significant speed-ups compared to previously-known variants of left-corner parsing. We also compare our method to several other major parsing approaches, and find that our improved left-corner parsing method outperforms each of these across a range of grammars. Finally, we also describe a new technique for minimizing the extra information needed to efficiently recover parses from the data structures built in the course of parsing.